PERANCANGAN DAN PEMBUATAN APLIKASI PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE JOB ORDER COSTING PADA PT. HASIL WINDU MAKMUR DI PACIRAN, LAMONGAN - Suryanto, Febry; Setiawan, Alexander; Rostianingsih, Silvia (Jurnal Infra, 2014)
PT. Hasil Windu Makmur is a companyengaged in breeding shrimp fry. PT. Hasil Macmur located inPaciran, Lamongan. These companies need information systemsthat can calculate the cost of production so that the work becomesmore effectives and efficients. This application was created byusing Microsoft Visual Studio 2005 VB. Net and SQL Server 2005as the database storage system . The method used in thecalculation of the cost of production is the job order costingmethod by using FIFO (First In First Out) on the stock feed andaverage on shrimp frieS. From the test results of applications,indicating that the application can process the data directlyrelated to the process of purchasing, production and salesautomatically. Report the cost of production and feed utilizationreports can be done quickly and accurately.